"Healing Alone?": Social Capital, Racial Diversity and Health Care Inequality in the American States. (November 2017) - Zhu, Ling
There is an influential tradition in political science that social capital, defined as mutual trust and civic engagement, is linked to better substantive outcomes for citizens in democracies. Recently, scholars who link social capital to race and inequality have challenged this favorable picture of social capital. This study draws from the scholarly discussion on how social capital affects inequality in diverse societies. Focusing on the health care domain, I use a new dynamic measure of social capital to evaluate the "social capital thesis" and "racial diversity thesis" of inequality. Moreover, I explore how these two political forces are intertwined with each other in shaping the unequal health care access across American states. Key empirical findings confirm that social capital and racial diversity are counterbalancing forces shaping health care inequality. Despite it reduces health care inequality, the impact of social capital is tempered with high level of racial diversity.